Long‐term follow‐up of chemoimmunotherapy with rituximab, oxaliplatin, cytosine arabinoside, dexamethasone (ROAD) in patients with relapsed CD20+ B–cell non‐Hodgkin lymphoma: Results of a study of the Mayo Clinic Cancer Center Research Consortium (MCCRC) MC0485 now known as academic and community cancer research united (ACCRU). Issue 10 (17th August 2017) - Witzig, Thomas E.; Johnston, Patrick B.; LaPlant, Betsy R.; Kurtin, Paul J.; Pederson, Levi D.; Moore Jr, Dennis F.; Nabbout, Nassim H.; Nikcevich, Daniel A.; Rowland, Kendrith M.; Grothey, Axel
Abstract: Patients with relapsed aggressive non‐Hodgkin lymphoma (NHL) are often treated with platinum‐based chemoimmunotherapy regimens in preparation for autologous stem cell transplant. We sought to reduce toxicity and maintain efficacy by using oxaliplatin with rituximab, cytarabine and dexamethasone (ROAD) in a phase II clinical trial in patients who had relapsed after one prior regimen. ROAD was delivered q21 days and consisted of rituximab 375 mg/m 2 IV weekly x 4 doses (cycle 1 only); dexamethasone 40 mg PO/IV d2 – 5; oxaliplatin 130 mg/m 2 IV day 2; cytarabine 2000 mg/m 2 IV × two doses on days 2 to 3; and pegfilgrastim 6 mg SC on day 4. Forty‐five eligible patients were accrued between 2006 and 2008. Patient characteristics were a median age of 69 years; 96% had received prior rituximab; 53% were within one year of diagnosis. The median number of cycles received was 2 (range, 1‐6). Forty‐four % received ROAD as an outpatient. The overall response rate was 71% with 27% (12/45) CR and 44% (20/45) PR. Forty‐four % (20/45) of all patients and 69% (18/26) of patients whom responded after 2 cycles proceeded to transplant. Median overall survival was 26 mos (95% CI: 7.3 mos—not reached) and median progression‐free survival was 11 mos (95% CI: 6—104 mos). There was no grade 3/4 nephrotoxicity; the rate of grade 3/4 neuropathy was 4%. Forty‐two percent of all patients and 69% of patients transplanted remain alive at 5 years. ROAD represents an acceptable salvage therapeutic option for patients with relapsed aggressive NHL.